A novel chitinase Chi6 with immunosuppressive activity promotes white spot syndrome virus (WSSV) infection in Penaeus vannamei. Issue 132 (January 2023) - Niu, Shengwen; Zhu, Yuening; Geng, Ran; Luo, Mengting; Zuo, Hongliang; Yang, Linwei; Weng, Shaoping; He, Jianguo; Xu, Xiaopeng
Abstract: Chitinases, a group of glycosylase hydrolases that can hydrolyze chitin, are involved in immune regulation in animals. White spot syndrome virus (WSSV) causes huge losses to crustacean aquaculture every year. We identified a novel chitinase Chi6 from Pacific white shrimp Penaeus vannamei, which contains a catalytic domain but no chitin-binding domain. The Chi6 expression was regulated by multiple immune signaling pathways and increased after immune stimulations. Silencing of Chi6 by RNAi in vivo did not affect Vibrio parahaemolyticus infection, but significantly increased the survival rate of WSSV-infected shrimp. The expression of multiple WSSV immediate early and structural genes was also decreased upon Chi6 silencing. The recombinant Chi6 protein showed no effect on bacterial growth but could attenuate shrimp hemocyte phagocytosis. The mRNA levels of several key elements and downstream genes of the MAPK and Dorsal pathways in Chi6-silenced shrimp were significantly up-regulated, suggesting an inhibitory effect of Chi6 on humoral immune response. Moreover, Chi6 enhanced the regulatory effect of Dorsal on the expression of WSSV ie1 gene. Therefore, Chi6 promotes WSSV infection through immunosuppression and regulation of WSSV gene expression. Targeting Chi6 could be a potential strategy for controlling WSSV disease in shrimp farming. Graphical abstract: Image 1 Highlights: The chitinase Chi6 from Penaeus vannamei is a target gene of multiple immune pathways. Chi6 suppresses hemocyte phagocytosis and expression of a set of immune related genes. Chi6 is involved in regulation of the Dorsal pathway. Silencing of Chi6 significantly reduce the susceptibility of shrimp to WSSV infection.